2020
DOI: 10.1186/s42397-020-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for plant height and fruit branch number based on RIL population of upland cotton

Abstract: Background: Plant height (PH) and fruit branch number (FBN) are important traits for improving yield and mechanical harvesting of cotton. In order to identify genes of PH and FBN in cotton germplasms to develop superior cultivars, quantitative trait loci (QTLs) for these traits were detected based on the phenotypic evaluation data in nine environments across four locations and 4 years and a previously reported genetic linkage map of an recombinant inbred line (RIL) population of upland cotton. Results: In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Plant architecture is related to traits such as yield and fiber quality and has an important impact on high yield and good quality ( Fu et al, 2019 ). Moreover, there are few QTL detected for PH in cotton, so it is necessary to use high-density genetic map to detect QTL for PH ( Li et al, 2013 ; Liu et al, 2020 ). In this study, we used the constructed high-density genetic map and QTL mapping based on the PH phenotype data of the five generations of F 9 –F 13 , and a total of 60 PH QTL were mapped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant architecture is related to traits such as yield and fiber quality and has an important impact on high yield and good quality ( Fu et al, 2019 ). Moreover, there are few QTL detected for PH in cotton, so it is necessary to use high-density genetic map to detect QTL for PH ( Li et al, 2013 ; Liu et al, 2020 ). In this study, we used the constructed high-density genetic map and QTL mapping based on the PH phenotype data of the five generations of F 9 –F 13 , and a total of 60 PH QTL were mapped.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the constructed high-density genetic map and QTL mapping based on the PH phenotype data of the five generations of F 9 –F 13 , and a total of 60 PH QTL were mapped. To identify the newly discovered QTL in this study, the upland cotton PH QTL included in CottonGen 5 ( Huang et al, 2017 ; Liu et al, 2020 ; Yu et al, 2021 ), and PH QTL identified in recent years ( Said et al, 2013 ; Huang, 2018 ; Su et al, 2018 ; Ma et al, 2019 ) were compared with the QTL of this work. The physical location of QTL is determined according to markers of confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing by Sanger's method is one of the earliest used methods for whole genome sequencing but is costly and time requiring that has limited its use in large populations. Because of rapidly developed high throughput sequencing techniques, a number of genetic maps have already been developed by using single nucleotide polymorphism (LIU et al 2020). Next generation sequencing (Singsit et al1997) technologies have covered the flaws of previous techniques and are now used widely in crop breeding field (Ray and Satya 2014).…”
Section: Sequencingmentioning
confidence: 99%
“…The steady growth of the human population and improvements in living standards have greatly increased the global demand for high-quality and healthier vegetable oil. Upland cotton is one of the most important industrial crops, which is not only the main source of natural fiber for the textile industry but is also an efficient protein, oil, and grain crop used for food or feed processing . Cottonseed, which possesses these properties, accounts for 60–70% of the total seed cotton weight .…”
Section: Introductionmentioning
confidence: 99%
“…Upland cotton is one of the most important industrial crops, which is not only the main source of natural fiber for the textile industry but is also an efficient protein, oil, and grain crop used for food or feed processing. 1 Cottonseed, which possesses these properties, accounts for 60−70% of the total seed cotton weight. 2 The kernel oil content (KOC) of cottonseed can be as high as 15.0%−48.7% of cottonseed weight and account for 15%−25% of cotton gross value, providing the fifth-largest source of vegetable oil for human consumption in the world.…”
Section: ■ Introductionmentioning
confidence: 99%